Asphaltene Precipitation Modeling of Sadi Formation in Halfaya Iraqi Oil Field - Ali Anwar Ali; Mohammed S. Al-Jawad; Abdullah A. Ali (Journal of Engineering, 2019)
Asphaltene is a component class that may precipitate from petroleum as a highly viscous and sticky material that is likely to cause deposition problems in a reservoir, in production well, transportation, and in process plants. It is more important to locate the asphaltene precipitation conditions (precipitation pressure and temperature) before the occurring problem of asphaltene deposition to prevent it and eliminate the burden of high treatment costs of this problem if it happens. There are different models which are used in this flow assurance problem (asphaltene precipitation and deposition problem) and these models depend on experimental testing of asphaltene properties. In this study, the used model was equation of state (EOS) model and this model depends on PVT data and experimental data of asphaltene properties (AOP measurement) and its content (asphaltene weight percent). The report of PVT and flow assurance of the live oil from the well (HFx1) of the zone of case study (Sadi formation in Halfaya oil field) showed that there is a problem of asphaltene precipitation depending on asphaltene onset pressure (AOP) test from this report which showed high AOP greater than local reservoir pressure. Therefore this problem must be studied and the conditions of forming it determined. In the present work, the asphaltene precipitation of Halfaya oil field was modeled based on the equation of state (EOS) by using Soave-Redlich-Kwong (SRK) equation which gave the best matching with the experimental data. The main result of this study was that the reservoir conditions (pressure and temperature) were located in the asphaltene precipitation region which means that the asphaltene was precipitated from the oil and when the pressure of the reservoir decreases more with oil production or with time it will cause asphaltene deposition in the reservoir by plugging the pores and reducing the permeability of the formation.